Amniotic Fluid Infection in Preterm Pregnancies with Intact Membranes. (12th January 2017) - Myntti, Tarja; Rahkonen, Leena; Nupponen, Irmeli; Pätäri-Sampo, Anu; Tikkanen, Minna; Sorsa, Timo; Juhila, Juuso; Andersson, Sture; Paavonen, Jorma; Stefanovic, Vedran
Abstract : Introduction . Intra-amniotic infection (IAI) is a major cause of preterm labor and adverse neonatal outcome. We evaluated amniotic fluid (AF) proteolytic cascade forming biomarkers in relation to microbial invasion of the amniotic cavity (MIAC) and IAI in preterm pregnancies with intact membranes. Material and Methods . Amniocentesis was made to 73 women with singleton pregnancies; 27 with suspected IAI; and 46 controls. AF biomarkers were divided into three cascades: Cascade 1: matrix metalloproteinase-8 (MMP-8), MMP-9, myeloperoxidase (MPO), and interleukin-6; Cascade 2: neutrophil elastase (HNE), elafin, and MMP-9; Cascade 3: MMP-2, tissue inhibitor of matrix metalloproteinases-1 (TIMP-1), MMP-8/TIMP-1 molar ratio, and C-reactive protein (CRP). MMP-8 was measured by an immunoenzymometric assay and the others were measured by ELISA. Standard biochemical methods, molecular microbiology, and culture techniques were used. Results . MMP-8, MMP-9, MPO, elafin, and TIMP-1 concentrations were higher in IAI suspected cases compared to controls and also in IAI suspected cases with MIAC compared to those without MIAC when adjusted by gestational age at amniocentesis. All biomarkers except elafin and MMP-2 had the sensitivity of 100% with thresholds based on ROC-curve. Odd ratios of biomarkers for MIAC were 1.2-38 and 95% confidential intervals 1.0-353.6. Conclusions . Neutrophil based AF biomarkers were associated with IAI and MIAC.